Chlorophyll Content of Aromatic Rice Mentik Susu in Peat Soils Due to Ash Ameliorant and Jakaba LOF - Zidani, Muhammad Aldy; Saputra, Riza Adrianoor; Jumar, Jumar; Nindhiani, Faridawati Junjung; Wijaya, Erlangga Nata (TROPICAL WETLAND JOURNAL, 2024)
Paddy plant chlorophyll is one of the determinants of plant growth and development, as photosynthesis plays a role in capturing light and transforming inorganic compounds into nutrients that plants need. The problem with the cultivation of paddy in the palm soil is the high saturation of the soil. There is a need for improvement in the ashes, ashes of palm powder, and empty palm cane ashes to lower the saturation. In addition, the application of jakaba LOF is necessary to boost the growth of milk dough crops, especially in the formation of chlorophyll. This research aims to determine the effect of jakaba LOF on the chlorophyll content of aromatic mentik susu rice in peat soil where ash ameliorant has been applied. This study used a nested factorial completely randomized design (CRD). The jakaba LOF application factor was nested in the type of ash ameliorant. The ameliorant type factor (s) consists of four treatments: s0 = no ameliorant, s1 = rice husk ash, s2 = sawdust wood ash, and s3 = empty oil palm bunch ash. The dose factor for LOF jakaba application (j) consists of two treatments: j0 = without application of LOF jakaba, j1 = application of LOF jakaba 15 mL-1. The results of the research showed that the application of LOF jakaba did not have a significant effect on the chlorophyll content of aromatic mentik susu rice in peat soil based on the type of ash ameliorant. Application of ash ameliorant to peat soil planted with milk aromatic rice can increase the chlorophyll b content and total chlorophyll of rice. Treatment without ash ameliorant (s0) can increase the chlorophyll b content and total chlorophyll content of rice by 16.45 mg mL-1 and 15.27 mg mL-1, respectively compared to the treatment of rice husk ash (s1), sawdust wood ash (s2), and empty palm fruit bunch ash (s3).